Peran Bimbingan dan Dukungan Keluarga terhadap Optimisme dalam Memperoleh Pekerjaan pada Fresh Graduate - Ernawati, Linda; Windy Aurellia (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2023)
Fresh graduates who have just finished their education in college will be required to immediately get a job. However, the COVID-19 pandemic has reduced the chances of getting a job. In dealing with this situation, social support from the family is needed to increase optimism. This study focuses on knowing the effect of each form of family social support on optimism in getting a job during the COVID-19 pandemic for fresh graduates of Nurtanio University. The method used is a quantitative method. Sampling using total sampling technique, with research subjects as many as 61 people. Collecting data through a questionnaire based on Sarafino's social support theory (2011) with a validity value of 0.463 - 0.849 and a reliability of 0.813 and Seligman's (2008) theory of optimism with a validity value of 0.585 - 0.887 and a reliability of 0.901. The results showed that the p-value of the four forms of social support was 0.000, meaning that there was a significant influence between the four forms of family social support on optimism, with details, namely: 1) Emotional support 28.9% (adj. R2 = 0.289). 2) Instrumental Support 27.7% (Adj. R2= 0.277). 3) Informational Support 36.8% (adj. R2= 0.368). 4) Friendship Support 31.2% (adj. R2= 0.312). Suggestions from this study are for families or parents to be able to balance the provision between the four forms of social support that exist, especially in the form of instrumental support so that the problems faced can be directly resolved and suggestions for further research that have an interest in similar topics in order to expand the reach of the population used.